If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + 2(p + -1) = 9p + 4 Reorder the terms: 3p + 2(-1 + p) = 9p + 4 3p + (-1 * 2 + p * 2) = 9p + 4 3p + (-2 + 2p) = 9p + 4 Reorder the terms: -2 + 3p + 2p = 9p + 4 Combine like terms: 3p + 2p = 5p -2 + 5p = 9p + 4 Reorder the terms: -2 + 5p = 4 + 9p Solving -2 + 5p = 4 + 9p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-9p' to each side of the equation. -2 + 5p + -9p = 4 + 9p + -9p Combine like terms: 5p + -9p = -4p -2 + -4p = 4 + 9p + -9p Combine like terms: 9p + -9p = 0 -2 + -4p = 4 + 0 -2 + -4p = 4 Add '2' to each side of the equation. -2 + 2 + -4p = 4 + 2 Combine like terms: -2 + 2 = 0 0 + -4p = 4 + 2 -4p = 4 + 2 Combine like terms: 4 + 2 = 6 -4p = 6 Divide each side by '-4'. p = -1.5 Simplifying p = -1.5
| 9+6k=5+4k | | G-21=20 | | 2x^2-48=80 | | y=-4(1)+7 | | 2x+5=-x+-1 | | 478.56=170+1.16x | | -5(p-2)=2(2p-5)+p | | -8(x-3)+4=-7(x-4)-x | | 11y=-12x-135 | | -217.636=6.2(-2.3-5.3x)+6.1x | | 4+n=19-2n | | 105=16x | | -5(r+6)=-96 | | 6(x-4)+6=4p-46 | | 3(2x+5)+2(x-4)=7 | | 0.6n-11=n+4 | | 25=r+16 | | (4)=3x+5 | | .8x-10=.2x+4 | | 0=n-15-n | | 2a-11=9 | | 8x-12=2x-48 | | 5+6q=9 | | y=-4(0)+7 | | -36=8-6p-7p | | 8=-4+u | | -1.2=-0.9u+0.6u | | 10b-2(b+3)=5b | | 4x-15=x+42 | | 1/2d-3/4=3/5 | | 3(4x-2)=21+5x | | (3)=3x+5 |